If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -5x + -3x = 7 + -5x + -2x Combine like terms: -5x + -3x = -8x 8 + -8x = 7 + -5x + -2x Combine like terms: -5x + -2x = -7x 8 + -8x = 7 + -7x Solving 8 + -8x = 7 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 8 + -8x + 7x = 7 + -7x + 7x Combine like terms: -8x + 7x = -1x 8 + -1x = 7 + -7x + 7x Combine like terms: -7x + 7x = 0 8 + -1x = 7 + 0 8 + -1x = 7 Add '-8' to each side of the equation. 8 + -8 + -1x = 7 + -8 Combine like terms: 8 + -8 = 0 0 + -1x = 7 + -8 -1x = 7 + -8 Combine like terms: 7 + -8 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| 90-x=2x+19 | | 1.2/5=7 | | 10n=96 | | 20x^2-10x-20=0 | | 187.5/x=10 | | X-9+2x=90 | | Sec^2x-2=-1 | | 150-(-37.5)=x | | 5(x+2)=3(x+1)-11 | | 5y-x=-35 | | bx-ax/x | | Sin(37)=x/15 | | 26-(-5)=-2x+10-x | | x^(1/7) | | K^2-20k+53=0 | | 11x-5=5x-47 | | 19=-5v-1 | | 3(2x)+4(6)-6x=-2(2x+2)+4 | | 4b+3b-2=19 | | 9x-6=3x+4 | | =8-2y | | 2(5x+12)-10x=-4(3x+3)+12 | | 6=4+5 | | 180=-4(3x-4)-16 | | 6z+z^2=16 | | 8b-2=2b+4 | | -8=2(x-5)+10 | | Log(5)(3x-2)=2 | | 7e^6x=193 | | ln(15x)-2ln(1+x)=ln(3) | | 7(3+y)=6(y-4) | | 5x+35=16 |